Breaking the chains: The inverted-U-shaped relationship between action-state orientation and creativity under low job autonomy - BLEDOW, Ronald (Institutional Knowledge at Singapore Management University, 2022)
When the social fabric of organizations limits individual autonomy, new ideas are needed that satisfy a person’s will as well as the constraints imposed by the social context. To explain when people achieve this synthesis and display creativity under low job autonomy, we examine the influence of their action-state orientation. The theory of action versus state orientation contrasts two responses people display when faced by a situation that conflicts with their will. An actionoriented response entails that people readily disengage from processing the situation and initiate goal-striving, while a state-oriented response entails that people remain focused on the situation. We argue that creativity under low job autonomy requires the integration of the competing processes underlying action and state orientation and is most frequently displayed by people in the midrange of the action-state orientation continuum. We test this theorizing with three studies. In a constrained laboratory setting, we induced a focus on an unwanted situation and demonstrated an inverted-U-shaped relationship between action-state orientation and creativity. A field study showed that the inverted-U-shaped relationship between action-state orientation and daily self-reports of creativity was strongest under low job autonomy and disappeared under high job autonomy. A multi-source study replicated and extended these relationships using managerial ratings of creativity.